2022
DOI: 10.4103/jcd.jcd_184_22
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of clinical performance of ceramic and resin inlays, onlays, and overlays: A systematic review and meta analysis

Abstract: Background: Advances in adhesive technologies and escalation in esthetic demands have increased indications for tooth-colored, partial coverage restorations. Recently, material knowledge has evolved, new materials have been developed, and no systematic review has answered the question posed by practitioners: Is the clinical efficacy of resin or ceramic better, for inlay, onlay, and overlay in the long run? Aim: The aim of this systematic review and meta-analysis was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The present study showed excellent and good qualities with 68% (in CGPCs) and 71.8% (in CIOs) for both types of restoration. There are no differences regarding the clinical performance or the survival of ceramic restorations in data pools from university teaching compared with data pools from private practice [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed excellent and good qualities with 68% (in CGPCs) and 71.8% (in CIOs) for both types of restoration. There are no differences regarding the clinical performance or the survival of ceramic restorations in data pools from university teaching compared with data pools from private practice [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In literature, there are numerous short-term and a few long-term data with high survival rates for teeth restored with ceramic partial crowns, mostly up to ten years. It was also reported that includable information on the survival of ceramic on- and overlays performing up to 15 years are barely available [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Currently, the main glass-ceramics used for inlays and onlays res- showed that the 5 years survival rate of glass-ceramics inlays and onlays were 92% and the 10 years survival rate were 89%, both higher than resin inlays (86%, 75%), the 5 years survival rate was higher than feldspathic porcelain (90%), and the 10 years survival rate did not differ from feldspathic porcelain (91%). 114 It is shown that glass-ceramics can provide good retention and aesthetic results in inlay restorations, improve the survival rate of restorations and (2 years), 90.37% (4 years), and 87.99% (5 years). 115 Yang et al 116 fabricated 6855 restorations with IPS e.max Press and the 5-year cumulative survival rate was 96.6%, Li 2 Si 2 O 5 glass-ceramics have a mechanical strength of 360-400 MPa, which not only meets clinical restoration requirements, but also has a high survival rate.…”
Section: Heat Pressed Techniquementioning
confidence: 99%
“…In a prospective study, the expected survival rate of IPS e.max CAD‐repaired inlays and onlays was longer (124 and 30 years, respectively, for a 10% failure rate) 113 . A retrospective study showed that the 5 years survival rate of glass‐ceramics inlays and onlays were 92% and the 10 years survival rate were 89%, both higher than resin inlays (86%, 75%), the 5 years survival rate was higher than feldspathic porcelain (90%), and the 10 years survival rate did not differ from feldspathic porcelain (91%) 114 . It is shown that glass‐ceramics can provide good retention and aesthetic results in inlay restorations, improve the survival rate of restorations and patient satisfaction, and gradually become the main choice for inlays and onlays restorations.…”
Section: Applications Of Glass‐ceramicsmentioning
confidence: 99%
“…Holmes defines the internal gap as the perpendicular measurement from the internal surface of the casting to the axial wall of the preparation, and the marginal gap as the same measurement at the margin [16]. Poor marginal fit decreases the long-term durability of the restorations, leading to microleakage, secondary caries, gingival inflammation, and cement dissolution, while insufficient internal fit increases the risk of fracture of the prothesis [17,18]. For marginal and internal fit evaluation, different methods are available, and they are distinguished mainly as destructive or non-destructive and 2D or 3D methods [19,20].…”
Section: Introductionmentioning
confidence: 99%